2015
DOI: 10.1021/id5000376
|View full text |Cite
|
Sign up to set email alerts
|

Carbacaprazamycins: Chemically Stable Analogues of the Caprazamycin Nucleoside Antibiotics

Abstract: Carbacaprazamycins, which are chemically stable analogues of caprazamycins, were designed and synthesized. These analogues were active against drug-resistant bacterial pathogens such as methicillin-resistant Staphylococcus aureus and vancomycin-resistant enterococci, and their activities were comparable to those of the parent caprazamycins. The effect of treatment with carbacaprazamycin on morphological changes in S. aureus indicated that the mode of action was completely different from those of existing pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 44 publications
0
38
0
1
Order By: Relevance
“…To date, several derivatives of uridylpeptide natural products have been generated through engineering of the organisms that produce the natural products or through semi-synthetic approaches and, as such, feature limited structural variation171819202122232425. A number of synthetic studies have also been reported on uridylpeptide natural products and analogues2627282930313233, some of which have been shown to possess antimicrobial activity78. The focus of the present study was to develop a rapid and divergent synthetic strategy to access a diverse library of sansanmycin analogues that would enable the determination of key structure-activity relationships specifically against Mtb.…”
Section: Resultsmentioning
confidence: 99%
“…To date, several derivatives of uridylpeptide natural products have been generated through engineering of the organisms that produce the natural products or through semi-synthetic approaches and, as such, feature limited structural variation171819202122232425. A number of synthetic studies have also been reported on uridylpeptide natural products and analogues2627282930313233, some of which have been shown to possess antimicrobial activity78. The focus of the present study was to develop a rapid and divergent synthetic strategy to access a diverse library of sansanmycin analogues that would enable the determination of key structure-activity relationships specifically against Mtb.…”
Section: Resultsmentioning
confidence: 99%
“…[102] As the oxazolidine analogues were revealed to be weak MraY inhibitors (IC 50 = 920-1200 mm), Ichikawa et al recently reported the carbacaprazamycin analogues,w ith MIC values of 4-16 mgmL À1 and MraY inhibition with IC 50 values of 2.6-6.9 nmol L À1 . [108] However,t he morphological changes observed in S. aureus indicated am ode of action that may be completely different from existing peptidoglycan inhibitors.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Assignment was based on 1 H-1 H COSY, HMBC and HMQC NMR spectra. 1 (22). 1-(6,7-Dideoxy-2,3-O-isopropylidene-β-D-allo-hept-6-enofranosyl)uracil (17).…”
Section: Methodsmentioning
confidence: 99%